Vancouver's Island, the new colony [electronic resource] - Fitzgerald, James Edward, 1818-1896 (London : Simmonds, 1848)
Cover title. "Reprinted from the 'Colonial Magazine' for August, 1841." Electronic reproduction. Mode of access: Internet. 44